Serum adiponectin levels in normotensive and pre-eclamptic women at the University College Hospital, Ibadan, Nigeria (2018)
Background: Adiponectin is a hormone produced mainly by adipocytes. The levels of adiponectin are inversely related to insulin resistance, hypertension and obesity. Physiological insulin resistance is exaggerated in pre-eclamptic women. The objective of the present study was therefore to compare serum adiponectin levels in pre-eclamptic patients and normotensive patients. Methods: This prospective study was conducted among one hundred and twenty women. Purposive sampling technique was used to select all consenting participants, consisting of sixty pre-eclamptic patients as cases and sixty normotensive pregnant women at comparable gestational age as control. Concentration of serum adiponectin was measured by using enzyme linked immunosorbent assay (ELISA) method. Results: Serum levels of adiponectin were significantly higher in the pre- eclamptic group(p<0.001). Body mass index was also significantly higher in women with pre eclampsia (p<0.01).In the pre-eclamptic patients, serum levels of adiponectin showed a weak negative correlation with BMI (r= -0.16, p= 0.22) and no correlation was found in normotensive patients. Conclusion: This study showed a clear distinction in the serum adiponectin concentration between preeclamptic and normotensive pregnant women. The impact of BMI on serum adiponectin in both groups also differs. Therefore, serum adiponectin may be useful in predicting pre-eclampsia.